2007
DOI: 10.1111/j.1468-0262.2006.00758.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Wald Tests for Fractional Unit Roots

Abstract: In this article we introduce efficient Wald tests for testing the null hypothesis of unit root against the alternative of fractional unit root. In a local alternative framework, the proposed tests are locally asymptotically equivalent to the optimal Robinson (1991Robinson ( , 1994a) Lagrange Multiplier tests. Our results contrast with the tests for fractional unit roots introduced by Dolado, Gonzalo and Mayoral (2002) which are inefficient. In the presence of short range serial correlation, we propose a simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(83 citation statements)
references
References 19 publications
(27 reference statements)
2
79
0
2
Order By: Relevance
“…Table 3 7 As in other standard large-sample tests, Wald and LR test statistics against fractional alternatives have the same null and limit theory as the LM test of Robinson (1994). Lobato and Velasco (2007) essentially employed such a Wald testing procedure, and, although this and other recent methods such as the one developed by Demetrescu et al (2008) have even been shown to be robust with respect to unconditional heteroscedasticity (Kew and Harris, 2009) [Insert Table 3 about here]…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 7 As in other standard large-sample tests, Wald and LR test statistics against fractional alternatives have the same null and limit theory as the LM test of Robinson (1994). Lobato and Velasco (2007) essentially employed such a Wald testing procedure, and, although this and other recent methods such as the one developed by Demetrescu et al (2008) have even been shown to be robust with respect to unconditional heteroscedasticity (Kew and Harris, 2009) [Insert Table 3 about here]…”
Section: Resultsmentioning
confidence: 99%
“…Other parametric methods for estimating d based on the frequency domain were proposed, among others, by Fox and Taqqu (1986) and Dahlhaus (1989) (see also Robinson, 1994 andLobato andVelasco, 2008 …”
Section: Methodsmentioning
confidence: 99%
“…Speci…cally, we focus on a modi…cation of the Fractional Dickey-Fuller (FDF) test by Dolado, Gonzalo and Mayoral (2002;DGM hereafter) recently proposed by Lobato and Velasco (2007;LV hereafter) which achieves a slight improvement in e¢ ciency over the former. This test, henceforth denoted as the EFDF (e¢ cient FDF) test, generalizes the traditional DF test of I(1) against I(0) processes without deterministic components to the broader framework of testing I(1) against I(d) with 0 d < 1.…”
Section: Introductionmentioning
confidence: 99%